Five Boarding School Activities in Educating Students' Character - Daulay, Winni Elmina; Lutfiyani, Lutfiyani; Rozaq, M. Abdur; Lestari, Prawidiya; Ramadhani, Mutiara Suci; Kaema, Muhammad Tolal (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2023)
One effort to shape the character of students is through activities at boarding school. These activities include; curricular, extracurricular, leadership, sports, social and humanitarian activities, arts and culture, health and welfare, and deliberation. Boarding schools can be part of a wider educational ecosystem to prepare children to become responsible, ethical citizens and have good social skills. This research aims to determine whether boarding school activities in educating the character of students in Islamic education institutions can produce strong and positive characters in everyday life. This research uses qualitative methods with a case study approach (case study design). Data sources were taken from thirty people consisting of; one principal, one curriculum representative, three dormitory supervisors, five parents of students, five members of the community, and fifteen students who were conducted using in-depth interviews were selected using the technique of purposive sampling. Furthermore, in this research, there are five boarding school activities in educating students' character in Islamic education institutions, including: first; extra-curricular activities form creative, independent, disciplined, and religious character. Second, sport: builds a healthy body and soul, appreciation for achievement, and enthusiasm. Third, social and humanitarian: hard work, tolerance, social concern, love of peace. Fourth, arts and culture: creativity, love of the country, responsibility. Fifth, religion: religion, discipline, independence, and responsibility. From the five boarding school activities, it is hoped that students will be accustomed to implementing strong Islamic religious-based character values ​​as preparations for future life.